Synthesis, characterization and solvatochromic behaviour of new water-soluble 8-hydroxy-3,6-disulphonaphthyl azohydroxynaphthalenes (2022)
A series of five tetracyclic mono azo dyes based on the diazotization of 1-amino-8-hydroxynaphthalene-3,6-disulphonic acid and subsequent coupling with substituted (un)sulphonated naphthalene derivatives have been synthesized. The chemical structures of the dyes were established using UV–visible, IR, NMR as well as mass spectrometry. Based on the number of sulphonic acid and other hydrophilic groups they contain, the compounds showed varying extent of water solubility. Spectroscopic characterization revealed the existence of azohydrazone tautomerism and the influence of the structures of solvating solvents on the equilibrium. Statistical analysis of single, dual and multiparametric equations of Kamlet Abboud and Taft parameters showed that solvent polarity was the most significant contributor to the observed spectral patterns of the dyes in pure solvents. The compounds could find useful applications as solvatochromic probes, food and drug colour additives.